An analysis of age bias against older workers in the recruitment and selection - Jingrui, Zhang (2020)
Age bias against older workers in recruitment and selection is always a serious problem in the organizations and society. The dilemma of older workers in employment and age bias they faced in recruitment process should be concerned. This qualitative research aims to search out the situation and the potential causes of age bias against older age group in recruitment and selection from the perspective of older workers. In order to achieve research aims, 10 purposed participants will be involved in the interview and some relevant information should be discussion based on the investigation and pervious literature. The result show that older workers face different degrees of age bias in recruitment and selection. For the reasons of age bias, they believe that stereotype of older age group is the main and root reason of the ageism and partly influence other causes such as attitudes and behaviors of employers, employment cost, nature of specific industries and job position they apply as well as legislation and functions of public. Moreover, these reasons are interrelated and influence each other. Meanwhile, based on the findings, some suggestion will be put forward to relieve this phenomenon and provide a more relaxed environment for the employment and employment of older workers.